Between pilgrims and tourists. The case of the alto de la Alianza Battlefield of the War of the Pacific (1880) - Vega-Centeno Alzamora, Patricia Milena (2024)
The battle of Alto de la Alianza or Campo de la Alianza (1880) is a crucial historical event in the development of the Tacna and Arica campaign, as well as a decisive factor in the outcome of the War of the Pacific (1879-1883). This research explores the development of tourist activity in this battlefield, as well as evaluates the components of the scenario, the role of historical heritage, the transformation of the war landscape over the years and aspects of the commemoration. Particularities that together show a dialogue with the historical memory and the tangible and intangible war heritage of this nineteenth-century conflict for the city of Tacna, turning it into a patrimonial space and reflection on the impact generated by war and its tragic consequences for society. The study methodology is descriptive, of an exploratory type, which shows that in the visits that take place in this battlefield there is also a pilgrimage component with a strong symbolic, cultural, and educational connotation for the population of Tacna through the commemoration annual reinforces its local identity.